2016
DOI: 10.1186/s12944-016-0385-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of palmitoleic acid on human lymphocyte proliferation and function

Abstract: BackgroundPalmitoleic acid (PA) is a n-7 monounsaturated fatty acid (MUFA) secreted by adipose tissue and related to decreased insulin resistance in peripheral tissues. Evidences have been shown that PA also decreased proinflammatory cytokine expression in cultured macrophages. Although studies have shown that other fatty acids (FAs) modulate several lymphocyte functions, the specific effect of PA on these cells is unknown. The aim of the present study was to evaluate the possible influence of PA on activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Dietary lipids modulate the innate and adaptive responses of immune system components [26][27][28][29]. In the present study, we showed that some FAs modulated proinflammatory gene expression in PBMCs and their ability to produce H 2 O 2 after 2 h stimulation with LPS.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Dietary lipids modulate the innate and adaptive responses of immune system components [26][27][28][29]. In the present study, we showed that some FAs modulated proinflammatory gene expression in PBMCs and their ability to produce H 2 O 2 after 2 h stimulation with LPS.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, omega-3 FAs can reverse low-grade inflammation in obesity by increasing the synthesis of pro-resolving mediators, such as resolvins, and decreasing proinflammatory mediators [33]. The mechanisms of FA effects on gene expression in PBMCs are not yet known, but it is probable that FAs can directly bind to membrane receptors or change intracellular protein activation [29], modulating TLRs [34] and NFκB [35] signaling pathways and, consequently, the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our results, Rocha et al demonstrate that MUFA high-fat meal consumption leads to a significant reduction in IL-17A postprandial response in healthy women with a high percentage of body fat (38) . Similarly, an in vitro study demonstrated an increase in IL-4 concentration after incubation with oleic acid, but not with palmitoleic acid (39) . Monocytes extracted from healthy men exhibit a higher concentration of IL-4 after acute consumption of a fat-enriched meal with MUFA and PUFA in comparison with the meal rich in SFA (40) .…”
Section: Discussionmentioning
confidence: 89%
“…In animal tissues, oleic acid is one of the most abundant free fatty acids regardless of tissue or species ( 4144 ), implying that tissue-resident T regs are sensing oleic acid, and that oleic acid may be an important signal for tissue-resident T regs . LCFAs can alter cellular proliferation and viability in a dose dependent manner ( 3, 4551 ). However, at a concentration of 10μM of oleic acid, we observe increases in FOXP3 expression (Supplemental Figure 1A-B), but do not find any differences in T reg viability (Supplemental Figure 1C) or proliferation (Supplemental Figure 1D) in the presence of either oleic acid or arachidonic acid compared to vehicle.…”
Section: Resultsmentioning
confidence: 99%